Drug-Induced Thrombocytopenia: Mechanisms and Laboratory Diagnostics - Danese, Elisa; Montagnana, Martina; Favaloro, Emmanuel J; Lippi, Giuseppe (Seminars in thrombosis and hemostasis, 2020)
Thrombocytopenia is a condition characterized by a decreased number of platelets in peripheral blood, which can be caused by a myriad of both congenital and acquired disorders. Drug-induced thrombocytopenia (DIT) deserves a special focus since its cumulative incidence can be as high as 10 cases per million population per year, with a prevalence of approximately 25% in critically ill patients. This condition is usually suspected following identification of an acute and severe decrease in platelet count, with values usually < 50 ×10 /L, thus potentially exposing patients to an increased risk of developing spontaneous hemorrhages. Conversely, however, some drug-related thrombocytopenias are instead (and perhaps counterintuitively) associated with increased thrombosis risk. Although a vast number of drugs have been implicated in DIT, the underlying pathogenetic mechanisms are essentially bifold, encompassing reduced platelet production due to bone marrow suppression (thus insufficient maturation or inefficient expansion of megakaryocytes, impaired release of platelets, or accelerated platelet apoptosis) or accelerated clearance of platelets from the circulation. This second form of DIT can be sustained by nonimmune, immune-mediated, or autoimmune mechanisms. An early and accurate diagnosis of DIT, which is crucial for reversing an otherwise unfavorable clinical outcome, is essentially based on the complete blood cell count, blood smear analysis, and performance of specific functional or immunochemical tests aimed at demonstrating the presence of antiplatelet antibodies.